A new two-phase rock typing approach: using wetting-phase relative permeability and critical pore size - Yokeley, Brandon A. (Kansas State University, 2021)
Rock typing, the methodology of grouping rocks based on their mineralogical, hydraulic, and/or petrophysical similarities has many applications in reservoir engineering, characterization, and simulation. Grouping rocks based on single-phase data has been widely discussed in the literature, while two-phase rock typing methodologies are limited. Single-phase rock typing methods generally identify rock types using porosity and permeability measurements based on similar characteristic pore sizes. To address the effect of wettability, ignored in single-phase rock typing, the present study focuses on classifying rock types using two-phase flow data. Using concepts from critical-path analysis (CPA) we propose a new rock typing methodology based on wetting-phase relative permeability curve, krw, critical pore radius, rc, and effective wetting-phase saturation, Se. For this purpose, we convert the wetting-phase relative permeability curves, Sw −krw, to Se −rc curves. We utilize a curve clustering method to identify representative rock types. To assess the proposed rock typing approach, we first created a large petrophysical dataset using pore network simulations, that covered a comprehensive range of pore size distributions, contact angles, pore coordination numbers, pore shape distributions, and clay contents. Overall, 240 pore networks were generated. We also simulated two-phase flow in six additional pore networks based on properties of Berea, Mt. Simon, and Fontainebleau sandstones. Results showed that there exist twelve unique rock types in our dataset. However, using single-phase rock typing techniques, we found a different number of rock types ranging between eight and fifteen depending on the methods applied. The discrepancies in the results of single- and two-phase rock typing approaches highlighted the importance of classifying rocks using two-phase flow data.
Keywords: Rock typing; Two-phase; Pore network modeling